Functional Food Development: Cassia fistula Stem Bark Ethanol Extract as a Potential Antioxidant and Anticancer Agent - Muhaimin, Muhaimin; Chaerunisaa, Anis Yohana; Lestari, Uce; Hirzan, Rifanza; Syahri, Wilda (Indonesian Food Science and Technology Journal, 2026)
This study investigates the pharmacological potential of Cassia fistula (Tilai), a plant traditionally used by Indonesian tribes as both medicine and food. The ethnobotanical significance of this species has inspired scientific exploration of its bioactive compounds. The ethanol extract of Cassia fistula stem bark demonstrated strong antioxidant activity, with an IC50 of 7.512 μg/mL, comparable to Vitamin C's IC50 of 4.716 μg/mL, indicating effective free radical scavenging. Additionally, the extract exhibited notable cytotoxicity against MCF-7 breast cancer cells, with an IC50 of 51.26 μg/mL. UHPLC-HRMS analysis revealed nine bioactive compounds, mainly flavonoids, phenolics, and quinones, which may contribute to its biological activities. These findings support the hypothesis that Cassia fistula stem bark contains potent antioxidant and anticancer constituents, highlighting its potential as a natural source for developing therapeutic agents. This research provides valuable insights into the phytochemical profile of Cassia fistula and its cytotoxic effects, encouraging further studies to explore its mechanisms and applications in cancer treatment.